Distribution of histological diagnoses of black and white skin in Campinas, diseases Brazil, from 1993 to 2009 - Isabela Mamere Alvarez; Juliana Puggina; Helymar C. Machado; Rafael Fantelli Stelini; Michelle Etienne Florence; Elemir Macedo de Souza; Maria Letícia Cintra (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2013)
INTRODUCTION: Little is known about ethnic differences in the frequency of skin diseases, and even less in terms of Brazilian population, which is characterized by miscegenation. OBJECTIVE: To evaluate the distribution of skin disorders in black and Caucasian patients through pathological specimens. METHODS: 826 biopsies from black-skinned individuals and 1,652 from white-skinned patients were retrieved and studied from the files of the Pathology Department, UNICAMP Hospital within the period of 1993-2009. The clinical data were obtained from medical records and the results were tested by statistical methods. RESULTS: Non-melanoma cancer was the most frequent diagnosis in Caucasians (45%), differing from the frequency among black patients (8%), both arising in sun-exposed skin. Regarding topography and age, in white-skinned patients aged over 50 years, biopsies of "head and neck" prevailed. As to black patients, the disease predominated among female individuals aged from 15 to 50 years and in the genital area. In the comparative analysis of vulvar diseases, we observed differences in diagnoses of sexually transmitted diseases more common among black women. Excluding cancers and genital lesions, black patients had a higher percentage of infectious diseases. Among the non-infectious diseases, cutaneous lupus was the most frequent diagnosis in both groups. Lichen planus and drug reactions were more frequent in black patients. CONCLUSION: Apart from intrinsic differences among skin types, social factors may interfere in the distribution of diseases. Not only may these results be useful to public health programs, but they may also aid the approach to dermatological diseases in black skin patients.